2021
DOI: 10.1007/s43440-021-00267-7
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory effect of olanzapine on SMIM20/phoenixin, NPQ/spexin and NUCB2/nesfatin-1 gene expressions in the rat brainstem

Abstract: Background Phoenixin, spexin and nesfatin-1 belong to a family of newly discovered multifunctional neuropeptides that play regulatory roles in several brain structures and modulate the activity of important neural networks. However, little is known about their expression and action at the level of brainstem. The present work was, therefore, focused on gene expression of the aforementioned peptides in the brainstem of rats chronically treated with olanzapine, a second generation antipsychotic drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
1
4
0
1
Order By: Relevance
“…Escitalopram does in turn not alter nesfatin-1 synthesis in the rat brain. This result stays in accordance with our recent observation showing that long-term treatment with olanzapine did not affect NUCB2 mRNA in the rat brainstem, while the gene expression of SMIM20/phoenixin and spexin was distinctly modulated [98]. Perhaps NUCB2 gene expression exposes relatively high stability in particular brain regions.…”
Section: Discussionsupporting
confidence: 93%
“…Escitalopram does in turn not alter nesfatin-1 synthesis in the rat brain. This result stays in accordance with our recent observation showing that long-term treatment with olanzapine did not affect NUCB2 mRNA in the rat brainstem, while the gene expression of SMIM20/phoenixin and spexin was distinctly modulated [98]. Perhaps NUCB2 gene expression exposes relatively high stability in particular brain regions.…”
Section: Discussionsupporting
confidence: 93%
“…Apart from their expression in the central nervous system, nesfatin-1 and phoenixin-14 serum concentrations were also positively correlated in patients with PCOS [34], further suggesting a physiological interaction between the two peptides. A recent publication studied the effects of the long-term olanzapine treatment on both NUCB2/nesfatin-1 and phoenixin/SMIM20 mRNA expression in rodent brains and showed an increased expression of phoenixin/SMIM20 with an unaltered NUCB2/nesfatin-1 level, falling in line with the anxiolytic and antidepressant properties of olanzapine, as well as supporting the notion of a counterbalancing role of phoenixin and nesfatin in depression/anxiety [98].…”
Section: Interactionsmentioning
confidence: 64%
“…The hypothalamic and supraventricular nuclei of the hypothalamus were able to play a crucial role in spexin development while contributing to water regulation, food intake, energy consumption, and reproductive behaviors. Spexin genes expression in the paraventricular and supraoptic nuclei of the hypothalamus similar to the nesfatin-1 receptor, were shown to be associated with oxytocin and corticotropin system ( Pałasz et al, 2021 ). Also, Recent studies have shown the interaction of GAL upsurges the polarization of serotonergic neurons outstanding to the receptor-receptor interaction with 5-HT1AR and decreases the binding affinity of the auto receptor after binding to serotonin ( Wang et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%